Effect of taxanes on the miR-106 and miR-200c expression in prostate cancer cells in vivo and in vitro - D. S. Plevako; M. S. Knyazeva; E. I. Sidina; M. V. Berkut; S. A. Reva; S. S. Tolmachev; A. S. Artemyeva; A. K. Nosov; A. V. Malek (Вестник урологии, 2023)
Introduction. A combination of antiandrogen and cytostatic drugs was justified in the neoadjuvant therapy of patients with high-risk prostate cancer (HiRPCa) in some clinical trials. The effectiveness of such therapy in each individual case depends on the sensitivity of cancer cells to the applied drugs. It makes possible the development of the new technologies to personalize therapeutic approach. MicroRNAs (miRNAs) are a class of regulatory molecules whose expression is altered in PCa cells and can be associated with the sensitivity/resistance of cancer cells to specific cytostatics, for instance, taxanes.Objective. To identify the potential-marker miRNAs of PCa cells sensitivity to taxanes.Materials and methods. Samples of PCa tissue (n. 56) obtained from patients underwent neo-adjuvant therapy (antiandrogen and taxanes) and radical prostatectomy; PCa cell lines (PC-3, DU-145, LNCap). Total RNAs isolation was carried out using miRNeasy FFPE Kit, LRU-100-50; miRCURY LNA miRNA Focus PCR Panel, All-MIR kits were used for semi-quantitative analysis of potentially marker microRNA molecules using sequential reverse transcription and PCR.Results. The effect of taxanes on PCa cells is associated with up-regulation of miR-106b expression and down-regulation of miR-200c expression in both in vivo and in vitro conditions.Conclusion. MiR-106b and miR-200c miRNAs are involved in the response of PCa cells to taxanes, and therapeutic modification of these molecules in PCa cells may present a potential strategy to increase their sensitivity to taxane-containing therapy. Appropriate innovative technology may be in demand in the treatment of HiRPCa-patients.